INDONESIA'S SIMULTANEOUS ELECTORAL SYSTEM UNDER HUMAN RIHTS AND DEMOCRACY: CHALLENGES AND OPPORTUNITIES - Suparto, Suparto; Ibnususilo, Efendi; Admiral, Admiral; Taufiqurrahman, Faishal (Universitas Syiah Kuala, 2024)
The 2024 simultaneous elections mark a significant milestone as they combine the selection of the President, Vice President, Legislative Members, and Regional Heads for enhanced effectiveness and efficiency. However, this innovative approach also presents a host of challenges. This article employs a normative legal research methodology, utilizing both statutory and conceptual frameworks. Data collection involved a comprehensive literature review of relevant laws and regulations pertaining to elections. The findings of this study reveal that the democratic process of simultaneous elections is far from flawless. Instances of power abuse by the DPR and prevalent money politics practices continue to persist. Such misconduct occurs among participants, organizers, and voters, ultimately undermining the intended goals of enhancing democracy and upholding human rights values through the implementation of simultaneous elections.